Delegation of expressions for distributed SNMP information processing - Lopes, Rui Pedro (2003)
Due to the scalability problems of SNMP, management distribution has been an important topic during the last years. The DISMAN workgroup propose a set of MIB modules to address this matter. One of the DISMAN modules has the capability of using expressions to perform decentralized processing of management information - the Expression MIB. Although it is essential to network management, the Expression MIB is not as well known as other DISMAN modules, such as the Script MIB, and not as available in terms of implementations. This paper focuses on the Expression MIB features, its implementation details and it also discusses, from a critical point of view, its functionality. It also proposes minor changes which can boost its application range and importance.